VD_FINDINFO HC / 2011 / 617 vom 24. August 2011 - VD Tribunal cantonal (2011)
MODIFICATION DES CIRCONSTANCES, JUGEMENT DE DIVORCE, NOUVEAU MOYEN DE FAIT | 286 al. 2 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 311 al. 1 CPC (CH)